2002
DOI: 10.1080/080352502753711678
|View full text |Cite
|
Sign up to set email alerts
|

Impact of topical oils on the skin barrier: possible implications for neonatal health in developing countries

Abstract: Our data suggest that topical application of linoleate-enriched oil such as sunflower seed oil might enhance skin barrier function and improve outcome in neonates with compromised barrier function. Mustard oil, used routinely in newborn care throughout South Asia, has toxic effects on the epidermal barrier that warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(122 citation statements)
references
References 29 publications
3
116
0
2
Order By: Relevance
“…The results obtained may have implication for the proposed industrial use of tobacco seed oil for paints or as an alternative diesel fuel (Crawford and Hilditch 1950;Giannelos et al 2002). In addition, the increase of linoleic acid, an essential FA for mammals, in plant seeds has interesting implications in dermatology (Letawe et al 1998;Darmstadt et al 2002) and nutraceutics, since it can be used to produce conjugated or long-chain polyunsaturated FAs (Hornung et al 2004;Graham et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained may have implication for the proposed industrial use of tobacco seed oil for paints or as an alternative diesel fuel (Crawford and Hilditch 1950;Giannelos et al 2002). In addition, the increase of linoleic acid, an essential FA for mammals, in plant seeds has interesting implications in dermatology (Letawe et al 1998;Darmstadt et al 2002) and nutraceutics, since it can be used to produce conjugated or long-chain polyunsaturated FAs (Hornung et al 2004;Graham et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…61,67,68 Mustard oil, when applied to a mouse model, was a statistically significant contributor to transepidermal water loss, causing deterioration of skin barrier function. 69 …”
Section: Newborn Is Not Dried or Wrapped Immediatelymentioning
confidence: 99%
“…Mustard oil, which is the most commonly used oil in South Asia, has been shown to damage skin barrier function, leading to increased transepidermal loss of water and heat. 68,69,80 Although massage with certain emollients may be beneficial, 5,81,82 frequent and prolonged environmental exposure during massage could result in cold stress. Thus, care needs to be taken to limit exposure during the massage process.…”
Section: Transportmentioning
confidence: 99%
“…Furthermore, Tegaderm s may be more cost-effective and convenient for use in NICUs when compared to humidified isolettes, though topical oils have also shown promise. 30 A randomized controlled trial would be useful to definitively assess the benefits of using Tegaderm s , as suggested by our findings.…”
Section: Discussionmentioning
confidence: 78%